Parallel authoritarian powers: an explanation of Mexico's authoritarian regime breakdown. Issue 3 (3rd April 2019) - Hernández Company, José Antonio
ABSTRACT: Many scholars suggest that dominant parties enhance authoritarian regime resiliency by regularizing and directing the distribution of spoils, careers, and policy among members of the authoritarian coalition. This article challenges this assertion by providing a novel mechanism to explain why, under stress, some dominant party regimes are more likely to break down than others. The argument posits that an autocracy's capacity to fend off systemic crises increases when elites who control the power to make decisions locate themselves in the same organization (for example, the military, the bureaucracy, a political party) as elites in charge of implementing these decisions. If elites of these types locate in different organizations (what I refer to as a "parallel power" arrangement), in the face of systemic adversities elite collective action suffers and, consequently, regime resiliency decreases. I illustrate the applicability of the argument in the case of Mexico's party-based autocracy. The stability of this regime was fatally damaged when, in the presence of systemic challenges in the 1980s and 1990s, the state's bureaucracy – in charge of making decisions – decided to enact economic and electoral policies against the wishes of the elites in the dominant party, who were in charge of implementing many of these decisions.